2016
DOI: 10.1002/2016rg000518
|View full text |Cite
|
Sign up to set email alerts
|

High‐latitude dust in the Earth system

Abstract: Natural dust is often associated with hot, subtropical deserts, but significant dust events have been reported from cold, high latitudes. This review synthesizes current understanding of high‐latitude (≥50°N and ≥40°S) dust source geography and dynamics and provides a prospectus for future research on the topic. Although the fundamental processes controlling aeolian dust emissions in high latitudes are essentially the same as in temperate regions, there are additional processes specific to or enhanced in cold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
257
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(297 citation statements)
references
References 264 publications
9
257
2
Order By: Relevance
“…Gobi desert) dust sources contribute the most global dust to the Northern Hemisphere (Luo et al, 2003). Several studies have found dust particles associated with LRT in snow and ice samples from the Canadian Arctic (Bullard et al, 2016;Groot Zwaaftink et al, 2016;Zdanowicz et al, 1998). Dust deposition to the Arctic shows a seasonal effect, with dust storms in major deserts occurring more frequently in the spring, leading to higher concentrations of mineral dust tracers in the spring and autumn (Barrie and Barrie, 1990 This could be caused by both mineral dust and PFAAs originating from the same regions.…”
Section: Elucidating the Role Of Marine-driven Transport Of Pfaas To mentioning
confidence: 99%
“…Gobi desert) dust sources contribute the most global dust to the Northern Hemisphere (Luo et al, 2003). Several studies have found dust particles associated with LRT in snow and ice samples from the Canadian Arctic (Bullard et al, 2016;Groot Zwaaftink et al, 2016;Zdanowicz et al, 1998). Dust deposition to the Arctic shows a seasonal effect, with dust storms in major deserts occurring more frequently in the spring, leading to higher concentrations of mineral dust tracers in the spring and autumn (Barrie and Barrie, 1990 This could be caused by both mineral dust and PFAAs originating from the same regions.…”
Section: Elucidating the Role Of Marine-driven Transport Of Pfaas To mentioning
confidence: 99%
“…These sources have significant local impacts-as does the North American Great Basin-but remain relatively minor on the global scale. There are also numerous locally significant areas of SDS activity in high-latitudes [23].…”
Section: The Scale Of Sds Impacts: Countries Affectedmentioning
confidence: 99%
“…Dust mobilization at high latitudes is strongly influenced by wind speeds, which are often quite strong in the presence of katabatic winds, sediment supply or dust availability, snow cover, freezing processes and vegetation (e.g. Bullard et al, 2016). The combination of these factors often leads to a strong seasonality in dust emission or dust storm frequency at high latitudes.…”
Section: Introductionmentioning
confidence: 99%